The Role of Gamification Mechanisms in CRM Systems in Enhancing Customer Loyalty: A Systematic Literature Review - Marvel Ravindra Dioputra; Herbert Siregar (Jurnal Indonesia Sosial Sains, 2026)
The advancement of digital technology has prompted organizations to adopt innovative approaches to customer relationship management, notably through the integration of gamification into Customer Relationship Management (CRM) systems. This study analyzes the role of gamification mechanisms within CRM systems and their contribution to enhancing customer loyalty using a Systematic Literature Review (SLR) approach, adhering to PRISMA guidelines. The review focuses on publications retrieved from reputable scientific databases between 2020 and 2025. The literature selection process identified five primary articles demonstrating that gamification mechanisms such as points, rewards, badges, leaderboards, and challenges effectively enhance customer engagement, experience, and satisfaction within CRM systems, thereby reinforcing customer loyalty. However, the effectiveness of gamification is contingent upon the design of the mechanisms, their alignment with user characteristics, and the digital readiness of the organization. This study concludes that gamification is an effective strategy for augmenting CRM functionality to cultivate customer loyalty, provided it is implemented in an integrated and customer-experience-oriented manner.